2009
DOI: 10.1007/s00125-009-1431-7
|View full text |Cite
|
Sign up to set email alerts
|

JNK3 is abundant in insulin-secreting cells and protects against cytokine-induced apoptosis

Abstract: Aims/hypothesis In insulin-secreting cells, activation of the c-Jun NH 2 -terminal kinase (JNK) pathway triggers apoptosis. Whereas JNK1 and JNK2 are ubiquitously produced, JNK3 has been described exclusively in neurons. This report aims to characterise the expression and role in apoptosis of the three JNK isoforms in insulin-secreting cells exposed to cytokines. Methods Sections of human and mouse pancreases were used for immunohistochemistry studies with isoformspecific anti-JNK antibodies. Human, pig, mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 47 publications
3
57
0
Order By: Relevance
“…JNK1 is the main contributor to cytokine-induced β cell apoptosis [45]. To clarify the role of these isoforms on viral replication, we used previously validated siRNAs targeting JNK1 or JNK2 [24, 45]. These siRNAs knocked down JNK1 and JNK2 protein expression by 55 and 65%, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…JNK1 is the main contributor to cytokine-induced β cell apoptosis [45]. To clarify the role of these isoforms on viral replication, we used previously validated siRNAs targeting JNK1 or JNK2 [24, 45]. These siRNAs knocked down JNK1 and JNK2 protein expression by 55 and 65%, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The siRNAs used were: Allstars Negative Control siRNA (siCTL, Qiagen, Venlo, The Netherlands), and rat JNK1 (siJNK1) [23], rat JNK2 (siJNK2) [24], and rat IRE1α (siIRE1α), all from Invitrogen, Carlsbad, CA, USA [25]. The protocol for siRNA transfection was previously validated using a FITC-coupled siRNA (siGLO Green Transfection Indicator, Thermo Scientific, Chicago, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…However, ␤-cells also express JNK3, and this may have protective roles, unlike those prodeath roles described for JNK1 or JNK2 (432). Thus, approaches targeting the JNKs as possible therapeutic strategies will need to consider both tissue-and isoform-specific differences.…”
Section: Jnk Actions In Insulin Resistance and Diabetesmentioning
confidence: 99%
“…Early studies indicated that these MAPKs, or at least some of their isoforms, are mainly localized in the nucleus of resting cells [70-72], and may be exported out to the cytoplasm upon stimulation [70]. However, it later became clear that in most cells and conditions they do behave similarly to ERK1/2, namely, localized mostly in the cytoplasm of resting cells, and translocate into the nucleus upon stimulation [73, 74].…”
Section: The Mechanism Of Mapks Translocation Into the Nucleusmentioning
confidence: 99%